By choice and by chance: assessing undergraduates hotel career commitment. - Nurashikin A Ridzuan (2015)
Undeniably,the significant major expansion in tourism and hospitality industry can clearly be seen in Malaysia and this has turned the hotel industry into one of the most important sectors in the country.This is evident when this industry contributes as the third largest foreign exchange revenue with many new opening thus creates demand for employment especially among the graduates with higher hospitality qualifications.This phenomenon lead to the proliferation of the public and private hospitality institutions in Malaysia with various related courses offering and two to threefold of students’ intake.Some students in the public hospitality institutions in particular are enrolling either By-Choice which isreferring a decision of individual school leavers of choosing or applying a program based on own desire,interest and qualification or By-Chance which is the method of offering the school leavers on the program that they are not applying but their qualification suit the program offered.Although the main intention of both modes is to increase the number graduate into the hospitality industry however those By-Chance students in particular might create an issue with regard to their future career commitment toward employment in hotel industry.This study is therefore aims to compare the hotel career commitment between By-Choice and By-Chance hospitality undergraduate students and investigate the relationship between hallmark and work value in hotel industry and the graduate’s commitment towards hotel career.Using the quantitative approach the hospitality undergraduate students who are currently undertaking hospitality programs at three Universiti Teknologi Mara campuses (Puncak Alam,Penang and Dungun) were surveyed.Through a series of analyses like inferential statistic (Independent sample t-test and standard multiple regressions),some useful insights on the issue investigated were obtained.Result revealed that the hallmarks of the hotel industry either nature of hotel career,pay and benefits,chances of promotion,co-workers,physical working condition and work value do not clearly influenced the hospitality undergraduate students career commitment.The most remarkable findings of this is that,if not all,the declining sentiment or reducing intentions to pursue such career among the UiTM hospitality undergraduate students are apparent regardless whether they were initially choosing the course (By-Choice ) or being offered with the course (By-Chance).This is evidence when there is no single difference between both By-Choice and By-Chance either on the hallmarks of the hotel industry and commitment toward career.These weakened employment intentions are formed during the educational programme and are probably at least partially a result of the maturation process and experience after undergone the practical training is giving varying consequences and implications for hospitality institutions,industry and the government.